Effects of Heart Rate Variability Biofeedback in Patients With Acute Ischemic Stroke: A Randomized Controlled Trial. Issue 1 (January 2020) - Chang, Wan-Ling; Lee, Jiunn-Tay; Li, Chi-Rong; Davis, Amy H. T.; Yang, Chia-Chen; Chen, Yu-Ju
Background: Autonomic dysfunction, cognitive impairment, and psychological distress are associated with poorer prognosis in patients with acute ischemic stroke (AIS). Heart rate variability (HRV) biofeedback (BF) improves autonomic dysfunction, cognitive impairment, and psychological distress in other patient populations, but its effect in patients with AIS is still unclear. Objective: This study investigated the effects of an HRVBF intervention on autonomic function, cognitive impairment, and psychological distress in patients with AIS. Method: In this randomized, controlled, single-blind trial, patients with AIS were randomly assigned to the experimental or control group. The experimental group received four HRVBF training sessions. The control group received usual care. Repeated measures of HRV, mini-mental status examination (MMSE), and Hospital Anxiety and Depression Scales (HADS) were collected prior to and at 1 and 3 months postintervention. Results: A total of 35 patients completed the study (19 experimental, 16 control). HRV and HADS significantly improved in the experimental group ( p < .001) but not in the control group. Likewise, only the experimental group showed significant improvements in HRV, MMSE, and HADS over time ( p < .05). Conclusion: HRVBF is a promising intervention for improving autonomic function, cognitive impairment, and psychological distress in patients with AIS. More studies of HRVBF interventions are needed to further optimize the effects of HRVBF on autonomic, cognitive, and psychological function in patients with AIS.